2-((5-Mercapto-1, 3, 4-thiadiazol-2-yl)thio)acetic acid as a novel chalcopyrite depressant for selective flotation separation of molybdenite from chalcopyrite. (15th June 2022) - Pan, Cheng-Lin; Wei, Xiang-Xiang; Zhang, Xu-Gang; Xu, Yong-Wei; Xu, Peng-Fei; Luo, Yong-Chun
Graphical abstract: Highlights: The use of 2-((5-mercapto-1, 3, 4-thiadiazol-2-yl)thio)acetic acid (MTAA) can effectively separate chalcopyrite and molybdenite. MTAA chemically adsorbed on the surface of chalcopyrite and had a stronger effect on chalcopyrite than on molybdenite. The interaction of MTAA with Cu sites on the surface of chalcopyrite is stronger than Fe sites. MTAA may react with copper ions to form a quaternary chelate structure via the S and N atoms. Abstract: In this work, 2-((5-mercapto-1, 3, 4-thiadiazol-2-yl)thio)acetic acid (MTAA), a stable and eco-friendly organic small-molecule reagent, was introduced as chalcopyrite depressant for selective flotation separation of molybdenite from chalcopyrite. In the flotation experiments of single mineral and artificially mixed mineral, the recovery of chalcopyrite reduces from 90% to 5% in the pH range of 5 to 10 when MTAA (8 mg/L) is added. The results of IR and zeta potential show that there are two tautomers (thione and thiol) in solid MTAA, while in aqueous solution, MTAA is mainly in the form of thiol and reacts with copper ions. The results of XPS and Tof-SIMS measurements indicate that MTAA may react with copper ions to form a quaternary chelate structure via the S and N atoms. The DFT calculation results also show that MTAA is more likely to react with copper ions than iron ions.